Potential and pitfalls of 1.5T MRI imaging for target volume definition in ocular proton therapy. (January 2021) - Via, Riccardo; Hennings, Fabian; Pica, Alessia; Fattori, Giovanni; Beer, Jürgen; Peroni, Marta; Baroni, Guido; Lomax, Antony; Weber, Damien Charles; Hrbacek, Jan
Highlights: The potential and pitfalls of target volume definition in ocular proton therapy based on Magnetic Resonance Imaging (MRI) were investigated and compared to the conventional clinical method based on metallic clips implantation on 33 uveal melanoma patients. In contrast to previous publications, an extensive description of discrepancies between the different modeling of the target volumes, together with a thorough investigation of the causes, is performed, as well as an investigation into the potential dosimetric consequences. For two out of thirty-three (6%) patients the lesion was invisible in MRI. Significant discrepancies between MRI and clips-based eye models were observed for tumor volume definition, with the MRI volumes being, on average, smaller than the clips-based one. Our results demonstrate that, independent of observer, while the height of MRI-based tumor volume agrees with the ultrasound assessment used in the conventional approach, inconsistencies in the definition of the base of the tumor between models produce the largest discrepancy in tumor volume definition. We observed a decrease of delineation discrepancies between radiation oncologists as a function of tumor size suggesting that, the bigger the lesion, the more visible it is on MRI images. Although the proposed MRI protocol has the potential to improve the accuracy of the eye model, on its own, it cannot replace the current clinical standard for target volume definition. However, the situation could change with the introduction of complementary ophthalmological imaging into the MRI approach in a geometrically accurate fashion. Abstract: Introduction: Ocular proton therapy (OPT) for the treatment of uveal melanoma has a long and remarkably successful history. This is despite that, for the majority of patients treated, the definition of the eye anatomy is based on a simplified geometrical model embedded in the treatment planning system EyePlan. In this study, differences in anatomical and tumor structures from EyePlan, and those based on 1.5T magnetic resonance imaging (MRI) are assessed. Materials and methods: Thirty-three uveal melanoma patients treated with OPT at our institution were subject to eye MRI. The target volumes were manually delineated on those images by two radiation oncologists. The resulting volumes were geometrically compared to the clinical standard. In addition, the dosimetric impact of using different models for treatment planning were evaluated. Results: Two patients (6%) presented lesions too small to be visible on MRI. Target volumes identified on MRI scans were on average smaller than EyePlan with discrepancies arising mostly from the definition of the tumor base. Clip-to-tumor base distances measured on MRI models exhibited higher discrepancy to ophthalmological measurements than EyePlan. For 53% of cases, treatment plans optimized for lesions identified on MRI only, failed to achieve sufficient target coverage for EyePlan volumes. Discussion: The analysis has shown that 1.5T MRI might be more susceptible to misses of flat tumor extension of the clinical target volume than the current clinical standard. Thus, a proper integration of ancillary imaging modalities, leading to a better characterization of the full lesion, is required.